Food Insecurity Among Farmworkers in Ventura County - Cedillo, Evelyn; Cortez, Joanna; Sanchez, Fabiola; Ambriz, Giselle; Angelez, Jose; Ibarra, Melissa; Cortez, Daniela; Garcia, Erick; Garcia, Jasmine; Gomez, Janitta; et al. (CBR@CSUCI: An annual volume of community-based research, 2025)
EXECUTIVE SUMMARY This community-based research project was a collaboration between Community Roots Garden and Sociology Capstone students. In March 2022, 100 farmworkers in Oxnard responded to survey questions about access to food. These surveys were administered by a group of ten students (Giselle Ambriz, Jose Angelez, Melissa Castro Ibarra, Evelyn Cedillo, Daniela Cortez, Erick Garcia, Janitta Gomez, Celeste Hernandez, Skye Loza, and Ana Rivera). The following semester, a group of five students (Joanna Cortez, Jasmine Garcia, Alexis Rodarte, Fabiola Sanchez, and Molly Velazquez) analyzed results to answer the research question: How does farmworker food insecurity vary by individual and household-level characteristics? We found that indigenous farmworkers face food insecurity at a significantly higher rate than other farmworkers. Overall, 62% of respondents indicated that they were food insecure. Yet, 78% of indigenous farmworkers in the study were food insecure compared to 48% of non-indigenous farmworkers. In addition, older farmworkers were more food insecure than younger farmworkers, as 75% of farmworkers 50 years old and above faced food insecurity. Not only do the farmworkers in the study face high rates of food insecurity, they also desire to eat more fruits and vegetables (99%), more organic food (97%), and more locally-grown food (99%) than they currently do. The majority of respondents know how to grow organically (64%), have experience growing for self-consumption (69%), and are interested in growing for self-consumption (73%), yet few currently do (19%). This is related to lack of access to land and underscores the importance of community gardens like Community Roots Garden in providing that access.